Problems of Tax Legislation Affecting the Development of Oil and Gas - Боднар, Г. Ф. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article aims to study the problems of tax laws that have influenced on the development of the oil and gas industry. Author determined the essential features of investment projects in the oil and gas industry, related to the fiscal regime. The attention to the importance of creating an attractive investment climate for the development of oil and gas industry through the use of a separate tax regime for projects that are implemented in terms of production sharing agreements. The problem of tax legislation are Highlighted. The effect of taxes on the oil and gas industry is developmented. Directions of improvement of fiscal management for the specified scope are outlined.